Polydimethylsiloxane / nanocellulose aerogel composite material and preparation method thereof

Through the preparation method of polydimethylsiloxane/nanocellulose aerogel composite, the problems of poor mechanical properties and insufficient thermal stability of cellulose aerogel are solved, and efficient and environmentally friendly water repellent and heat repellent are achieved. Improved stability and is suitable for the field of water-repellent thermal insulation.

CN119219979APending Publication Date: 2024-12-31YANCHENG INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411560948.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The application of existing cellulose aerogels in catalysis, adsorption, fuel cells and other fields is limited by their poor mechanical properties and insufficient thermal stability, and the use of organic solvents in solvent replacement method leads to environmental pollution and low efficiency.

Method used

Using the preparation method of polydimethylsiloxane/nanocellulose aerogel composite, the nanocellulose aerogel is freeze-dried in distilled water, and then immersed in polydimethylsiloxane prepolymer Bacetic acid Bake in the ester solution, and recover the volatile ethyl acetate using a condenser tube to avoid the use of a large amount of organic solvents.

Benefits of technology

A composite material with excellent water repellent properties, thermal stability and flame retardant properties is obtained. It is simple to operate, high efficiency, and is non-toxic and pollution-free, and is suitable for the field of water repellent thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219979A_ABST
    Figure CN119219979A_ABST
Patent Text Reader

Abstract

The invention relates to a polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof, and belongs to the field of material processing. The preparation method comprises the following steps: uniformly stirring a nano-cellulose suspension, freeze-drying the nano-cellulose suspension to prepare nano-cellulose aerogel, drying and dehydrating the nano-cellulose aerogel, pouring a prepared ethyl acetate solution of a polydimethylsiloxane prepolymer into a container in which the nano-cellulose aerogel is placed, dipping and defoaming, and drying to obtain the nano-cellulose aerogel. Putting a curing agent into a container, fully stirring, taking out the nanocellulose aerogel, baking, and in the baking process, connecting an air outlet of a baking oven with a condensation pipe device for condensing and recycling volatilized ethyl acetate, so as to obtain the polydimethylsiloxane / nanocellulose aerogel composite material. The aerogel composite material prepared by the method has excellent water repellency, mechanical property and thermal stability, meanwhile, the preparation method is high in speed and efficiency, and the organic solvent can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polydimethylsiloxane (PDMS) / nanocellulose aerogel composite material and a preparation method thereof, and belongs to the field of material processing. Background Art

[0002] Cellulose aerogel is a green and biodegradable nanoporous material. It has the excellent properties of silica aerogel and polymer aerogel, such as low density, high specific surface area, high porosity, etc., and at the same time has the unique properties of natural cellulose aerogel itself, which makes cellulose aerogel have good application value in catalysis, adsorption, fuel cells, thermal insulation and other fields. Because cellulose aerogel has good hydrophilicity, poor mechanical properties and poor thermal stability, its wider application is limited. In view of these situations, it is necessary to develop nanocellulose-based aerogel composite materials with excellent water repellency, mechanical properties and thermal stability. In the reports of the composite of polydimethylsiloxane and nanocellulose in the prior art CN201810762125.6, CN201810762178.8 and other public prior art and literature, polydimethylsiloxane / nanocellulose composite membrane materials were prepared by solvent replacement. A large amount of organic solvent is used in the solvent replacement process. It takes a long time for the organic solvent to gradually replace the water completely. The use of organic solvents will also have potential harm to the environment. Therefore, it is necessary to invent a polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof. The polydimethylsiloxane / nanocellulose aerogel composite material prepared by the method has excellent water repellency, mechanical properties and thermal stability. At the same time, the preparation method is fast and efficient, and the organic solvent can be recycled and reused. The present invention provides a polydimethylsiloxane / nanocellulose aerogel composite material with very good application prospects in the field of water repellent thermal insulation. Summary of the invention

[0003] The present invention aims at the deficiencies of the prior art and provides a polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof. The method comprises the following steps: diluting a nanocellulose suspension with distilled water, stirring it evenly and then freeze-drying it to prepare the nanocellulose aerogel, placing the nanocellulose aerogel in a container for drying and dehydration, and after the nanocellulose aerogel is dehydrated, pouring a prepared polydimethylsiloxane prepolymer ethyl acetate solution of a certain concentration into a container in which the nanocellulose aerogel is placed, and after the nanocellulose is quickly immersed in the polydimethylsiloxane prepolymer ethyl acetate solution, taking out the container, dipping and degassing, and placing a certain amount of catalyst in the polydimethylsiloxane prepolymer ethyl acetate solution, stirring sufficiently and reacting, taking out the nanocellulose aerogel, and placing it in an oven for baking. During the oven baking process, a condenser device is connected to the oven outlet to condense and recover the volatilized ethyl acetate. After baking, the polydimethylsiloxane / nanocellulose aerogel composite material can be obtained. The polydimethylsiloxane / nanocellulose aerogel composite material prepared by the present method has excellent water repellency, thermal stability and flame retardant properties. The method is simple and easy to operate, has high preparation efficiency, and the solvent is recyclable, thus avoiding the use of a large amount of organic solvents for replacement, and is green, environmentally friendly, non-toxic, and pollution-free.

[0004] The present invention specifically relates to a polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof. Figure 1 As shown, the specific steps are:

[0005] (1) Dissolving the nanocellulose suspension in deionized water to prepare a nanocellulose solution with a concentration of 1 to 1.2%.

[0006] (2) introducing the nanocellulose suspension prepared in step (1) into a mold and freezing the suspension at a temperature of -40°C to -80°C. After the freezing is completed, placing the suspension in a freeze dryer for treatment. After the treatment is completed, taking out the suspension to obtain the nanocellulose aerogel.

[0007] (3) The nanocellulose aerogel obtained in step (2) is taken out and placed in a beaker, and then placed in an oven for drying at a temperature of 100° C. to 105° C. for 3 to 4 hours.

[0008] (4) Putting the polydimethylsiloxane prepolymer into ethyl acetate to prepare an ethyl acetate solution of the polydimethylsiloxane prepolymer. The weight percentage concentration of the ethyl acetate solution of the polydimethylsiloxane prepolymer is 5% to 7%.

[0009] (5) After the drying in step (3) is completed, the oven is opened, and the ethyl acetate solution of polydimethylsiloxane prepared in step (4) is quickly introduced into the beaker containing the nanocellulose aerogel, and then the beaker is taken out of the oven and vacuum degassed at room temperature for 15 to 20 minutes.

[0010] (6) Add the curing agent dropwise into the beaker in the vacuum degassing step (5), and stir at room temperature for 30 minutes at a stirring speed of 300 to 400 rpm. The weight ratio of the curing agent to the polydimethylsiloxane is 1:10.

[0011] (7) The nanocellulose aerogel stirred in step (6) is taken out and placed in an oven for baking. After baking, a polydimethylsiloxane aerogel / nanocellulose aerogel composite material is obtained. The exhaust port of the oven is connected to a condensing device to condense and recover the ethyl acetate volatilized by heat.

[0012] Beneficial effects of the present invention:

[0013] (1) The polydimethylsiloxane aerogel / nanocellulose aerogel composite material obtained by the method of the present invention has excellent water repellency, thermal stability and flame retardancy, and the water contact angle reaches 144° to 151°;

[0014] (2) The preparation method of the present invention uses simple materials, low cost, simple and easy operation, no solvent is required in the treatment process, thus avoiding the use of a large amount of organic solvents, and the treatment time is short. The organic solvent can be recycled during the baking process, which is green, environmentally friendly, non-toxic and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Flow chart for the preparation of polydimethylsiloxane (PDMS) / nanocellulose aerogel composites;

[0016] Figure 2 This is a photo of the polydimethylsiloxane / nanocellulose aerogel composite material of the present invention;

[0017] Figure 3 This is a SEM photo of the polydimethylsiloxane / nanocellulose aerogel composite material of the present invention;

[0018] Figure 4 For contact angle test comparison;

[0019] Figure 5 This is a TG test comparison chart. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0021] The actual object and SEM image of the polydimethylsiloxane / nanocellulose aerogel composite material of the present invention are as follows Figure 2-3 shown.

[0022] Example 1: A polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof, the specific steps are:

[0023] (1) Dissolve the nanocellulose suspension in deionized water to prepare a nanocellulose polymer suspension with a solution concentration of 1%.

[0024] (2) introducing the nanocellulose suspension prepared in step (1) into a mold and freezing the suspension at a temperature of -40°C. After the freezing is completed, placing the material in a freeze dryer for treatment. After the treatment is completed, taking out the material to obtain the nanocellulose aerogel.

[0025] (3) The nanocellulose aerogel obtained in step (2) is taken out and placed in a beaker, and then placed in an oven for drying at a drying temperature of 100° C. for 3 hours.

[0026] (4) Putting the polydimethylsiloxane prepolymer into ethyl acetate to prepare an ethyl acetate solution of the polydimethylsiloxane prepolymer. The weight percentage concentration of the ethyl acetate solution of the polydimethylsiloxane prepolymer is 5%.

[0027] (5) After the drying in step (3) is completed, the oven is opened, and the ethyl acetate solution of polydimethylsiloxane prepared in step (4) is quickly introduced into the beaker containing the nanocellulose aerogel, and then the beaker is taken out of the oven and vacuum degassed for 15 minutes.

[0028] (6) Add the curing agent dropwise into the beaker in the vacuum degassing step (5), and stir at room temperature for 30 minutes at a stirring speed of 300 rpm. The weight ratio of the curing agent to the polydimethylsiloxane is 1:10.

[0029] (7) The nanocellulose aerogel stirred in step (6) is taken out and placed in an oven for baking. After baking, a polydimethylsiloxane aerogel / nanocellulose aerogel composite material is obtained. The exhaust port of the oven is connected to a condensing device to condense and recover the ethyl acetate volatilized by heat.

[0030] Example 2: A polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof, the specific steps are:

[0031] (1) Dissolve the nanocellulose suspension in deionized water to prepare a nanocellulose polyvinyl alcohol solution with a concentration of 1.1%.

[0032] (2) introducing the nanocellulose suspension prepared in step (1) into a mold and freezing the suspension at a temperature of -60°C. After freezing, placing the suspension in a freeze dryer for treatment. After treatment, taking the suspension out to obtain the nanocellulose aerogel.

[0033] (3) The nanocellulose aerogel obtained in step (2) is taken out and placed in a beaker, and then placed in an oven for drying at a drying temperature of 102° C. for 3.5 hours.

[0034] (4) Putting the polydimethylsiloxane prepolymer into ethyl acetate to prepare an ethyl acetate solution of the polydimethylsiloxane prepolymer. The weight percentage concentration of the ethyl acetate solution of the polydimethylsiloxane prepolymer is 6%.

[0035] (5) After the drying in step (3) is completed, the oven is opened, and the ethyl acetate solution of polydimethylsiloxane prepared in step (4) is quickly introduced into the beaker containing the nanocellulose aerogel, and then the beaker is taken out of the oven and vacuum degassed for 18 minutes.

[0036] (6) Add the curing agent dropwise into the beaker in the vacuum degassing step (5), and stir at room temperature for 30 minutes at a stirring speed of 350 rpm. The weight ratio of the curing agent to the polydimethylsiloxane is 1:10.

[0037] (7) The nanocellulose aerogel stirred in step (6) is taken out and placed in an oven for baking. After baking, a polydimethylsiloxane aerogel / nanocellulose aerogel composite material is obtained. The exhaust port of the oven is connected to a condensing device to condense and recover the ethyl acetate volatilized by heat.

[0038] Example 3: A polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof, the specific steps are:

[0039] (1) Dissolve the nanocellulose suspension in deionized water to prepare a nanocellulose suspension with a solution concentration of 1.2%.

[0040] (2) introducing the nanocellulose suspension prepared in step (1) into a mold and freezing the suspension at a temperature of -80°C. After freezing, placing the suspension in a freeze dryer for treatment. After treatment, taking the suspension out to obtain the nanocellulose aerogel.

[0041] (3) The nanocellulose aerogel obtained in step (2) is taken out and placed in a beaker, and then placed in an oven for drying at a drying temperature of 105° C. for 4 hours.

[0042] (4) Put the polydimethylsiloxane prepolymer into ethyl acetate to prepare an ethyl acetate solution of the polydimethylsiloxane prepolymer. The weight percentage concentration of the ethyl acetate solution of the polydimethylsiloxane prepolymer is 7%.

[0043] (5) After the drying in step (3) is completed, the oven is opened, and the ethyl acetate solution of polydimethylsiloxane prepared in step (4) is quickly introduced into the beaker containing the nanocellulose aerogel, and then the beaker is taken out of the oven and vacuum degassed for 20 minutes.

[0044] (6) Add the curing agent dropwise into the beaker in the vacuum degassing step (5), and stir at room temperature for 30 minutes at a stirring speed of 400 rpm. The weight ratio of the curing agent to the polydimethylsiloxane is 1:10.

[0045] (7) The nanocellulose aerogel stirred in step (6) is taken out and placed in an oven for baking. After baking, a polydimethylsiloxane aerogel / nanocellulose aerogel composite material is obtained. The exhaust port of the oven is connected to a condensing device to condense and recover the ethyl acetate volatilized by heat.

[0046] The performance of the polydimethylsiloxane / nanocellulose aerogel composite material prepared in Example 1-3 was tested and compared with the existing nanocellulose aerogel. The results are as follows: Figure 4 shown.

[0047] from Figure 4 The contact angle test results show that after the water droplets are dropped onto the surface of the nanocellulose aerogel, the water droplets quickly penetrate into the material surface and no droplet shape can be observed, reflecting that the surface of the nanocellulose aerogel has excellent hydrophilic properties. The contact angles of the three embodiments are all around 147° on average, and can even exceed 150°. When the contact angle is not less than 150°, it is considered that the material has super hydrophobic properties, so the composite material prepared by the present invention has excellent water repellent properties.

[0048] Table 1 Comparison of strength and elongation test results

[0049] project Elongation at break / % Breaking strength / KPa Nanocellulose aerogel 2.34 43.17 Example 1 10.09 222.11 Example 2 12.46 279.24 Example 3 13.89 319.23

[0050] It can be seen from the breaking strength and breaking elongation test results that the breaking elongation and breaking strength of Examples 1-3 increased by at least 5 times, indicating that compared with the nanocellulose aerogel, the prepared composite material of the present invention has excellent mechanical properties.

[0051] from Figure 5It can be seen that the TG curves of Examples 1-3 show the first weight loss at about 350°C, and the second weight loss at about 550°C, while the first weight loss caused by the adsorbed water molecules appears at about 100°C for the nanocellulose aerogel, and the second weight loss appears at about 350°C, and the second weight loss is greater than the second weight loss of Examples 1-3. Therefore, the thermal stability of Examples 1-3 is significantly higher than that of the nanocellulose aerogel, which also reflects that the polydimethylsiloxane / nanocellulose aerogel prepared by the present invention has excellent thermal stability. At the same time, it can be seen from the TG graph of the material at about 100°C in the TG graph that none of Examples 1-3 has the first weight loss caused by the adsorbed water in the nanocellulose aerogel, which shows that the preparation method of the present invention is effective relative to the organic solvent replacement method mentioned in the prior art and the literature, and also shows that the present method can avoid the use of a large amount of organic solvents and the problem of very low failure rate when using solvent replacement, thereby improving the preparation efficiency.

[0052] The above embodiments verify the validity and practicality of the present invention. Although the present invention has been shown and described with reference to specific preferred embodiments, it should not be interpreted as a limitation of the present invention itself. Various changes can be made to it in form and detail without departing from the spirit and scope of the present invention defined in the appended claims.

Claims

1. A polydimethylsiloxane / nanocellulose aerogel composite material and a preparation method thereof, characterized in that: The specific steps of the method are: (1) A nanocellulose polymer solution is prepared with a concentration of 1 to 1.2%. (2) introducing the nanocellulose suspension prepared in step (1) into a mold and freezing the suspension at a temperature of -40°C to -80°C. After the freezing is completed, placing the suspension in a freeze dryer for treatment. After the treatment is completed, taking out the suspension to obtain the nanocellulose aerogel. (3) The nanocellulose aerogel obtained in step (2) is taken out and placed in a beaker, and then placed in an oven for drying at a temperature of 100° C. to 105° C. for 3 to 4 hours. (4) Putting the polydimethylsiloxane prepolymer into ethyl acetate to prepare an ethyl acetate solution of the polydimethylsiloxane prepolymer. The weight percentage concentration of the ethyl acetate solution of the polydimethylsiloxane prepolymer is 5% to 7%. (5) After the drying in step (3) is completed, the oven is opened, and the ethyl acetate solution of polydimethylsiloxane prepared in step (4) is quickly introduced into the beaker containing the nanocellulose aerogel, and then the beaker is taken out of the oven and vacuum degassed for 15 to 20 minutes. (6) Add the curing agent dropwise into the beaker in the vacuum degassing step (5), and stir at room temperature for 30 minutes at a stirring speed of 300 to 400 rpm. The weight ratio of the curing agent to the polydimethylsiloxane is 1:

10. (7) The nanocellulose aerogel stirred in step (6) is taken out and placed in an oven for baking. After baking, a polydimethylsiloxane aerogel / nanocellulose aerogel composite material is obtained. The exhaust port of the oven is connected to a condensing device to condense and recover the ethyl acetate volatilized by heat.

Citation Information

Patent Citations

  • Polydimethylsiloxane / nanocellulose composite membrane and preparation method thereof

    CN109054061A

  • Nanocellulose / carbon nanotube / polydimethylsiloxane conductive composite film and preparation method thereof

    CN109251342A